The Underlying Mechanism of Modulation of Transient Receptor Potential Melastatin 3 by protons - Hossain Saad, Md Zubayer; Xiang, Liuruimin; Liao, Yan-Shin; Reznikov, Leah R.; Du, Jianyang (Frontiers in Pharmacology, 2021)
Transient receptor potential melastatin 3 channel (TRPM3) is a calcium-permeable nonselective cation channel that plays an important role in modulating glucose homeostasis in the pancreatic beta cells. However, how TRPM3 is regulated under physiological and pathological conditions is poorly understood. In this study, we found that both intracellular and extracellular protons block TRPM3 through its binding sites in the pore region. We demonstrated that external protons block TRPM3 with an inhibitory pH50 of 5.5. whereas internal protons inhibit TRPM3 with an inhibitory pH50 of 6.9. We identified three titratable residues, D1059, D1062, and D1073, at the vestibule of the channel pore that contributes to pH sensitivity. The mutation of D1073Q reduced TRPM3 current by low external pH 5.5 from 62 ± 3 % in wildtype to 25 ± 6.0 % in D1073Q mutant. These results indicate that D1073 is essential for pH sensitivity. In addition, we found that a single mutation of D1059 or D1062 enhanced pH sensitivity. In summary, our findings identify molecular determinants responsible for the pH regulation of TRPM3. The inhibition of TRPM3 by protons may indicate an endogenous mechanism governing TRPM3 gating and its physiological/ pathological functions.